Recent progress on the phytotoxic effects of hydrochars and toxicity reduction approaches. (July 2022) - Karatas, Okan; Khataee, Alireza; Kalderis, Dimitrios
Abstract: Hydrothermal carbonization of wet biomasses has been known to produce added-value materials for a wide range of applications. From catalyst substrates, to biofuels and soil amendments, hydrochars have distinct advantages to offer compared to conventional materials. With respect to the agricultural application of hydrochars, both positive and negative results have been reported. The presence of N, P and K in certain hydrochars is appealing and may contribute to the reduction of chemical fertilizer application. However, regardless of biomass, hydrothermal carbonization results in the production of phytotoxic organic compounds. Additionally, hydrochars from sewage sludge often contain heavy metal concentrations which exceed the regulatory limits set for agricultural use. This review critically discusses the phytotoxic aspects of hydrochar and provides an account of the substances commonly responsible for these. Furthermore, phytotoxicity reduction approaches are proposed and compared with each other, in view of field-scale applications. Graphical abstract: Image 1 Highlights: The recent literature was reviewed regarding the phytotoxic effects of hydrochars. Acute phytotoxicity is attributed to furans, polyaromatic hydrocarbons and carboxylic acids. In the case of sewage sludge hydrochar, reduced crop growth is attributed to the presence of heavy metals. Hydrochar washing, microbial aging and co-composting are the main phytotoxicity reduction methods.